The rise of early Rome - Fulminante, Francesca. (Cambridge ; New York)
xviii, 268 sayfa
Keywords: “The trajectory of Rome from a small village in Latium vetus, to an emerging power in Italy during the first millennium BC, and finally, the heart of an Empire that sprawled throughout the Mediterranean and much of Europe until the 5th century CE, is well known. Its rise is often presented as inevitable and unstoppable. Yet the factors that contributed to Rome's rise to power are not well understood. Why Rome and not Veii? In this book, Francesca Fulminante offers a fresh approach to this question through the use of a range of methods. Adopting quantitative analyses and a novel network perspective, she focuses on transportation systems in Etruria and Latium Italy from ca. 1000-500 BC. Fulminante reveals the multiple factors that contributed to the emergence and dominance of Rome within these regional networks, and the critical role they in the rise of the city and, ultimately, Roman imperialism” --